The heat treatment effect on the surface characteristics of 9310 steel gear. Issue 1 (February 2020) - Ren, S Y; Wang, C Q; Zhang, W; Li, Y
Abstract: Gear is one of the key parts of aviation industry. With the rapid development of the aviation industry, the design and precision of gears, in particular 9310 steel ones, are permanently improved. This paper focuses on the heat treatment effect on the surface performance of 9310 steel gear. The heat treatment simulation of aviation gear is carried out the DEFORM-3D software. The effects of quenching and tempering temperature on the surface hardness and residual stress of gear are analyzed, which provides a theoretical basis for the heat treatment improvement of 9310 steel gear.